Aspek-aspek tidak patuh syariah dalam amalan jampi di Malaysia / Juriah Mohd Amin, PM Dr Huzaimah Ismail and PM Supani Husain - Mohd Amin, Juriah; Ismail, PM Dr Huzaimah; Husain, PM Supani (2015)
The arrival of Islam in the Malay world has brought a transformation of the traditional medical aspects as well as other aspects. As revealed religions, Islam emphasizes of halal and haram in all aspects, including medicine. Thus, any practice that is contrary to the principles of faith or morals or contrary to the Quran, Sunnah, ijma and qias is illegal. Today there are those who offer traditional medicine whether by individuals or organizations. But there are many non-Islamic elements when it is done with medication practices approach does not apply. Thus this paper aim to explore the various elements and the results of this study suggest that the authorities should establish specific guidelines for this alternative therapy. It aims to keep the Muslims from the elements that destroy their faith.